LEXICAL PRESUPPOSITION OF IKA VALENSIA THEORY IN POLICE INVESTIGATION REPORT - Ika Arifianti (Universitas Muhammadiyah Semarang, 2021)
Police interrogation reports are part of the investigator's authority. Investigators carry out interrogations in in order to do their duties and functions as a state apparatus. Pragmatic studies can be used in assessing the language used in Police investigation report. This study focuses on lexical presuppositions in police investigation report. Lexical presupposition is The use of one form with its asserted meaning is conventionally interpreted with the presupposition that another (non-asserted) meaning is understood and involving the lexical items, stop, start, and again. The lexical presupposition of Ika Valensia's theory is a development of the main theory of Levinson (1985), which was later developed by Rustono (1998), Ika Arifianti (2019) completed with the presupposition of Ika Valensia which gave rise to functions such as the development of Austin theory (1962) which was developed and refined by his student, Searle (1969). Descriptive form of human behavior that violates the law can lead to criminal acts. This unpleasant behavior is included in the complaint offense case category. A complaint offense case is a case related to defamation, slander, or other behavior deemed unpleasant. Responsible linguists are needed to uncover the potential for serious injustices in the judicial process.